Clinical and biochemical characteristics of familial type 1 diabetes mellitus (FT1DM) compared to non-familial type 1 DM (NFT1DM) - Alyafei, Fawzia; Soliman, Ashraf; Alkhalaf, Fawziya; Sabt, Aml; De Sanctis, Vincenzo; Elsayed, Nagwa; Waseef, Reem (Acta Biomedica Atenei Parmensis, 2018)
Introduction: Familial type 1 diabetes mellitus (FT1DM) comprises parent-offspring and sib-pair subgroups. The clinical and genetic characteristics of FT1DM cases with and without affected family members have been previously studied with varying results. Some investigators found similarity of presenting features whereas others reported significant differences between the two groups. Objective: To describe the clinical and biochemical characteristics of children with FT1DM in comparison with those with non-familial type 1 diabetes mellitus (NFT1DM). Patients and Methods: We performed a cross-sectional retrospective study in a cohort of children and adolescents with T1DM (n=424) aged between 6 months - 16 years attending to Hamad General Hospital Pediatric Diabetes Center, Doha (Qatar) from 2012-2016. They were divided into 2 groups. Group 1 consisted of 62 children and adolescent with FT1DM (parent-offspring or sib-pair). The other group (Group 2) consisted of 431 children and adolescents with NFT1DM. The clinical presentation and prevalence of β-cell autoimmunity (anti-glutamic acid decarboxylase (GAD) antibodies , anti-islet cell and anti-insulin antibodies), thyroid function (Free thyroxine: FT4 and thyroid-stimulating hormone: TSH), anti-thyroid peroxidase antibody (TPO) and anti-tissue transglutaminase (ATT) at their first presentation were recorded, described and analyzed. Results: FT1 DM was more prevalent in boys versus girls (1.4:1, respectively) whereas the prevalence of NFT1DM did not differ between genders (1:1.1, respectively). F1DM occurred relatively early in childhood (40.7% before the age of 4 years and 72% before 9 years of age) versus NFT1DM which occurred relatively later in life (80% after the age of 4 years and 40% after the age of 9 years). 35.2% of FT1DM presented with diabetic ketoacidosis (DKA) versus 32.5% of T1DM patients. Anti-islet antibodies (Ab) were detected more frequently in FT1DM versus NFT1DM. The prevalence of positive anti-insulin and anti- GAD antibodies did not differ between the two groups. Anti TPO were detected in 27.2% of NFT1DM and 35.5% of FT1DM. A primary hypothyroidism, with positive ATPO, was more prevalent in FT1DM versus NFT1DM. ATT IgA was high in 5% of NFT1DM and 19.8% of FT1DM whereas ATT IgG was high in 4.4 % of NFT1DM and 15.4% of FT1DM. Conclusions: FT1DM is more prevalent in boys versus girls and occurs earlier in childhood compared to NFT1DM. Primary hypothyroidism was more prevalent in NFT1DM versus FT1DM. Anti-islet Ab and ATT antibodies were more prevalent in the FT1DM versus NFT1DM. The genetic background may explain some differences between FT1DM and NFT1DM including the age of onset, gender affection, as well as associated autoimmune disorders.